2021
DOI: 10.1111/jonm.13510
|View full text |Cite
|
Sign up to set email alerts
|

Hospital nurses experiencing day‐to‐day workplace incivility: A diary study on the benefits of daily social support

Abstract: Aim The present study investigated the adverse effects of daily experienced incivility and the positive role of daily social support during the workday in predicting daily emotional exhaustion after work and vitality and positive affect at bedtime. Background Despite the broad knowledge of the impact of experienced incivility in different occupations, little is known about day‐to‐day nurse incivility, much less in the hospital context. Method After completing a general questionnaire, hospital nurses (n = 96) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Also making it difficult to compare and contrast frequency findings was the variation in the instruments' response time frames, which ranged from as long as the past 2 years (Smith et al, 2010) to as short as during the current day (Blanco‐Donoso et al, 2019; Carmona‐Cobo & Lopez‐Zafra, 2021). The original Workplace Incivility Scale asked respondents to answer the questions based on the previous 5 years (Cortina et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Also making it difficult to compare and contrast frequency findings was the variation in the instruments' response time frames, which ranged from as long as the past 2 years (Smith et al, 2010) to as short as during the current day (Blanco‐Donoso et al, 2019; Carmona‐Cobo & Lopez‐Zafra, 2021). The original Workplace Incivility Scale asked respondents to answer the questions based on the previous 5 years (Cortina et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that WI adversely affects both work outcomes (Jawahar and Schreurs, 2018) and non-work outcomes (Zhou et al, 2019); its prevalence has surrounded various sectors, including manufacturing (Wu et al, 2014) and service. In the service sector, WI research has been majorly reported in healthcare (Armstrong, 2018;Bar-David, 2018;Carmona-Cobo and Lopez-Zafra, 2021), education (Sakurai and Jex, 2012) and hospitality (Aljawarneh and Atan, 2018;Jin et al, 2020). Despite the fact that WI has been widely studied and investigated in a variety of areas, the current study was prompted by three key facts.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, WI research specific to the IT workplace has been neglected from such explorations while other workplaces healthcare (Bar-David, 2018;Armstrong, 2018;Carmona-Cobo and Lopez-Zafra, 2021) in the same sector were given due attention. Similar to Cho et al (2016), Shafran-Tikva et al (2017 found that explicit threats and verbal violence onto healthcare professionals primarily represented the influence of patients' and their companions' WI.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations